Stress analysis on the free-end distal extension of an implant-supported mandibular complete denture - Gustavo Diniz Greco; Wellington Corrêa Jansen; Janis Landre Junior; Paulo Isaías Seraidarian (Sociedade Brasileira de Pesquisa Odontológica, 2009)
A comparative and qualitative analysis of the tensions generated in the cantilever region of an implant-supported mandibular complete denture was conducted using the three-dimensional finite element method. The mechanical properties of the components were input in the model and a load of 15 N was applied in pre-determined points. In the first simulation, the load was applied on the occlusal surface of the first premolar. In the second simulation, it was applied on the first and second premolars. In the third simulation, it was applied on the first and second premolars and on the first molar. The different occlusion patterns produced similar tension distributions in the cantilever region, which followed a similar pattern in the three simulations. In all of the cases, the highest levels of tension were located in the region of the first implant. However, as the loads were dislocated distally, the tensions increased considerably. The more extensive the cantilever, the more compromised will be the infrastructure, the prosthetic components and the implants. Regardless of the length of the cantilever, the highest tensions will always be located in the region of the implant next to the load application point.